Current diagnostic and therapeutic strategies for the management of lymphatic insufficiency in patients with hypoplastic left heart syndrome - Bauer, Christoph; Dori, Yoav; Scala, Mario; Tulzer, Andreas; Tulzer, Gerald (Frontiers in Pediatrics, 2023)
Children with hypoplastic left heart syndrome share unique hemodynamic features that alter lymphatic integrity at all stages of palliation. Lymphatic congestion is almost universal in this patient group to some extent. It may lead to reversal of lymphatic flow, the development of abnormal lymphatic channels and ultimately decompression and loss of protein rich lymphatic fluid into extra lymphatic compartments in prone individuals. Some of the most devastating complications that are associated with single ventricle physiology, notably plastic bronchitis and protein losing enteropathy, have now been proven to be lymphatic in origin. Based on the new pathophysiologic concept new diagnostic and therapeutic strategies have recently been developed. Dynamic contrast magnetic resonance lymphangiography is now mainstay in diagnosis of lymphatic insufficiency and allows a thorough assessment of anatomy and function of the main lymphatic compartments through intranodal, intrahepatic and intramesenteric lymphatic imaging. Contrast enhanced ultrasound can evaluate thoracic duct patency and conventional fluoroscopic lymphangiography has been refined for evaluation of patients where magnetic resonance imaging cannot be performed. Novel lymphatic interventional techniques, such as thoracic duct embolization, selective lymphatic duct embolization and liver lymphatic embolization allow to seal abnormal lymphatic networks minimally invasive and have shown to resolve symptoms. Innominate vein turn-down procedures, whether surgical or interventional, have been designed to reduce lymphatic afterload and increase systemic preload effectively in the failing Fontan circulation. Outflow obstruction can now be managed with new microsurgical techniques that create lympho-venous anastomosis. Short term results for all of these new approaches are overall promising but evidence is sparse and long-term outcome still has to be defined. This review article aims to summarize current concepts of lymphatic flow disorders in single ventricle patients, discuss new emerging diagnostic and therapeutic strategies and point out lacks in evidence and needs for further research on this rapidly growing topic.